2021
DOI: 10.3389/fmicb.2021.660901
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Host Interactions: EGFR and Host Cell Signaling Is a Point of Convergence Between Viral Infection and Functional Changes in Infected Cells

Abstract: Viruses have evolved diverse strategies to manipulate cellular signaling pathways in order to promote infection and/or persistence. Human cytomegalovirus (HCMV) possesses a number of unique properties that allow the virus to alter cellular events required for infection of a diverse array of host cell types and long-term persistence. Of specific importance is infection of bone marrow derived and myeloid lineage cells, such as peripheral blood monocytes and CD34+ hematopoietic progenitor cells (HPCs) because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 201 publications
(401 reference statements)
0
2
0
Order By: Relevance
“…In this scenario, monocytes would be the target population due to their role in dissemination and as reservoir of latent viruses ( Collins-McMillen et al, 2018 ). Upon productive HCMV infection of monocytes, various signaling pathways are induced, among which a key role is played by EGFR-mediated induction of PI(3)K, Akt, N-WASP, NF-κB, and Sp-1, promoting survival and differentiation (reviewed in Lee et al, 2021 ). Monocytes express the activatory receptors, FcγRI, FcγRIIa, and FcγRIIIa, the latter only in 10% of the monocytes, and the inhibitory receptor, FcγRIIb.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, monocytes would be the target population due to their role in dissemination and as reservoir of latent viruses ( Collins-McMillen et al, 2018 ). Upon productive HCMV infection of monocytes, various signaling pathways are induced, among which a key role is played by EGFR-mediated induction of PI(3)K, Akt, N-WASP, NF-κB, and Sp-1, promoting survival and differentiation (reviewed in Lee et al, 2021 ). Monocytes express the activatory receptors, FcγRI, FcγRIIa, and FcγRIIIa, the latter only in 10% of the monocytes, and the inhibitory receptor, FcγRIIb.…”
Section: Discussionmentioning
confidence: 99%
“…Although subsequent work has indicated that EGFR is more likely to function as a co-receptor [ 148 ], EGFR has initially been proposed as an HCMV entry receptor [ 149 ]. HCMV-induced signaling through the EGFR has been recognized as a key control point for virus–host cell interaction and regulation of both viral and cellular activities [ 150 ]. In addition to EGFR, other receptors such as the platelet-derived growth factor receptor alpha (PDGFRα), Neuropilin-2, olfactory receptor family 14 subfamily I member 1 (OR14I1), and specific integrins and adhesion molecules have been shown to be crucial for HCMV entry [ 151 , 152 , 153 ].…”
Section: Cellular Determinants and Mechanism Of Syncytium Formationmentioning
confidence: 99%